2016
DOI: 10.1016/j.chemosphere.2015.12.095
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cathode material on electrochemical degradation of trichloroethylene in aqueous solution

Abstract: In this study, different cathode materials were evaluated for electrochemical degradation of aqueous phase trichloroethylene (TCE). A cathode followed by an anode electrode sequence was used to support reduction of TCE at the cathode via hydrodechlorination (HDC). The performance of iron (Fe), copper (Cu), nickel (Ni), aluminum (Al) and carbon (C) foam cathodes was evaluated. We tested commercially available foam materials, which provide important electrode surface are and properties for field application of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Fe electrodes were immersed in 1M HCl to remove any foreign metals and surface oxide layers. The palladization procedures for Fe and Cu foam were performed under the conditions given in Rajic et al, 2016. The Pd content at Fe and Cu was 0.5 mg cm −2 of geometric electrode surface area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe electrodes were immersed in 1M HCl to remove any foreign metals and surface oxide layers. The palladization procedures for Fe and Cu foam were performed under the conditions given in Rajic et al, 2016. The Pd content at Fe and Cu was 0.5 mg cm −2 of geometric electrode surface area.…”
Section: Methodsmentioning
confidence: 99%
“…This approach has been developed to use as in situ groundwater technology to remove trichloroethylene (TCE) from groundwater, and we found that nitrates presence adversely influences TCE removal. We found that nitrate presence adversely affects TCE hydrodechlorination by using a cathode followed by an anode sequence (Rajic et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TCE and nitrate are removed through the electrode-based electrochemical processes at cathode surface, therefore their removal efficiencies are subject to the factors that are related to the mass transfer effect of contaminants on electrode/liquid interface, such as hydraulic residence time and surface area of the electrode [6]. According to previous studies, a flow-through cell with the cathode placed in front of the anode with respect to the flow direction, nitrate presence adversely affects TCE hydrodechlorination by using a cathode followed by an anode sequence [9]. Further study by Lu et al (2010) on TCE degradation in the presence of nitrate indicated that higher nitrate concentration directed to an increased amount of precipitates that acted as a physical barrier and slowed degradation rate of TCE.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the costly materials used and the intriguing catalytic properties of nanomaterials, electrocatalysis on shape‐controlled noble metal nanoparticles has received an increasing attention for the reductive dehalogenation over the past several years, e. g., For instance, the Pd NPs loaded on different supporting materials exhibit remarkable electrocatalytic hydro‐dechlorination performances for the various aryl chlorides including chlorophenols and chlorophenoxyacetic acids, where the exposed (111) facets was considered to be highly active for triggering the reductive dechlorination reactions …”
Section: Critical Factors For Controlling the Electroreductive Dehalomentioning
confidence: 99%